A study on burden among caregivers of stroke patients - Abdul Hadi, Azwanis; Zainal Abidin, Muhammad 'Adil; Ismail, Mohd Nizamuddin; Ahmad, Imran (International Islamic University Malaysia, 2016)
Studies have shown that caregiving is associated with high burden that could affect caregivers' mental and physical well-being. Unfortunately, caregivers are often overlooked even by healthcare professionals. With the rise of our elderly population and morbidity from stroke, there is a need to assess the burden among caregivers in our society. This study was carried out to determine the level of burden among caregivers of Stroke patients attending Hospital University Sains Malaysia in Kelantan and to evaluate the possible risk factors associated with those with a burden.